Interstitial dup(6)(q22.3q24) characterized by cCGH resulting from familial inv ins(6)(p11.2q25.3q22.3): case report - Oliva Teles, Natália (2013)
Abstrat publicado em: European Journal of Human Genetics. 2003;21(Suppl 2):480